Is It Possible for Children with Dual Citizenship to Get Inheritance Rights in Indonesia? - Massie, Fitri Hidayah (Universitas Negeri Gorontalo, 2024)
This study aims to determine and analyze how the legal settlement process in Indonesia is related to the inheritance rights of children with dual nationality. Researchers use normative juridical research. The analysis technique used is descriptive analysis, namely by analyzing by describing the regulations related to the position of inheritance rights of children with dual nationality. The results of this study are that Indonesia does not yet have special rules regarding the Inheritance Rights of Children with Dual Nationality, especially in International Civil Law which explains that the regulation of inheritance law follows the national law of the heir. Therefore, couples who enter into a mixed marriage must pay more attention to what impacts will be faced in the future if this event occurs because Law Number 12 of 2006 concerning Citizenship also only regulates the status of children from mixed marriages, namely children will be given the privilege of having limited dual citizenship and then when they are 18 years old the child is free to choose whether to follow the citizenship of the father or mother, regarding other rights the law in Indonesia has not regulated clearly